Meaning of English Loanwords in Indonesian Articles of Sport - Ari Nurweni (UPP FIB UGM (No.02;Juni 2013;Vol.25), 2013)
Meaning of English Loanwords in Indonesian Articles of Sport: kata pinjaman dari bahasa inggris,perubahan makna,wacana tulis